Illegal Eel Trade ... : Illegaler Aalhandel ... - Stein, Florian (Universitätsbibliothek Braunschweig, 2025)
The illegal trade in European eels (Anguilla anguilla) has been identified as one of the most significant wildlife crimes globally, in terms of both the quantity of specimens traded and the profits generated. However, this specific wildlife crime remained rather unnoticed by the public, only receiving attention following a series of high-profile arrests and seizures in the mid-2010s which coincided with the first scientific investigations. In chapter 1, the research gap was identified and the background on the life history of eels, exploitation, as well as eel aquaculture was provided. Subsequently, it was explored why eel trade became one of the most significant wildlife crimes and how authorities responded to it. Chapter 2 (Kaifu et al., 2019) examines the extent of glass eel trafficking, which is estimated to account for approximately a quarter of the European eel stock. Furthermore, the chapter provides an overview of notable enforcement operations and examines the relationship between glass eel ... : Der illegale Handel mit Europäischen Aalen (Anguilla anguilla) ist eines der bedeutendsten Wildtierverbrechen, sowohl in Bezug auf die Menge der gehandelten Fische als auch auf die erzielten finanziellen Gewinne. Erst als Mitte der 2010er Jahre eine Reihe von hochkarätigen Verhaftungen und Beschlagnahmungen mit ersten wissenschaftlichen Untersuchungen zusammenfielen, gelangte das Thema in die Öffentlichkeit. Kapitel 1 widmet sich der Identifizierung von Forschungslücken und liefert eine Zusammenfassung grundlegender Informationen zur Biologie, Fischerei und Aquakultur von Aalen. Anschließend wird herausgearbeitet, warum der Aalhandel zu einem der bedeutendsten Wildtierverbrechen wurde und wie Behörden darauf reagierten. Kapitel 2 (Kaifu et al., 2019) untersucht das Ausmaß des illegalen Glasaalhandels. Es wird geschätzt, dass etwa ein Viertel des europäischen Aalbestandes jährlich illegal nach Asien exportiert wird. Darüber hinaus bietet das Kapitel einen Überblick über bedeutende Polizeioperationen und ...